(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Renal parenchymal disease is a growing global public health concern. Renal biopsy remains the gold standard for evaluating renal parenchymal disease, particularly in cases of nephrotic syndrome, proteinuria, glomerular hematuria. However, ultrasonography offers a noninvasive method to assess renal morphology. Objective: To correlate renal ultrasonographic parameters with histopathology in predicting irreversible renal parenchymal disease. Methods: This cross-sectional study conducted over two years (March 2022 to February 2024) includes 82 adult patients (³18 years),in the Department of Radiology and Imaging who were referred for image-guided renal biopsy. Renal sonographic findings were compared to biopsy findings, including glomerular sclerosis, interstitial inflammation, fibrosis, and tubular atrophy. Results: Most of the patients were middle aged and with a predominance of comorbid condition like hypertension (67.1%) and diabetes mellitus (54.9%). Grade 2 renal cortical echogenicity was the most common sonographic finding (58.5%). Renal cortical echogenicity demonstrated strong positive correlations with glomerular sclerosis (r = 0.568), interstitial inflammation (r = 0.493), interstitial fibrosis (r = 0.365), and tubular atrophy (r = 0.394), all statistically significant (p < 0.001). Renal length showed significant inverse correlations with these histopathological parameters (r ranging from -0.231 to -0.521; p <0.05). The combination of kidney length <9 cm and cortical echogenicity ³liver predicted irreversible renal parenchymal disease with a sensitivity of 93.3%, specificity of 94.0%, positive predictive value of 77.8%, negative predictive value of 98.4%, and overall diagnostic accuracy of 93.9%. Conclusion: Ultrasonography is a valuable tool for predicting irreversible renal parenchymal disease by assessing renal length and echogenicity with high diagnostic accuracy in correlation with histopathology, supporting it’s use in clinical evaluation of suspected glomerulonephritis.